Real-Time Rendering Algorithm Based On Hybrid Static And Dynamic Simplification Methods - Pan, Zhigeng; Zhou, Kun; Shi, Jiaoying (International Journal of Virtual Reality, 2001)
Level of detail (LoD) method is a key technique for real-time rendering. The generation algorithms of LoD models may be divided into two categories: static or view-independent algorithms and dynamic or view-dependent algorithms, each has its own advantages and drawbacks. This paper presents a new realtime rendering algorithm incorporating both of the two kinds. We simplify polygonal models viewindependently according to a user-specified approximation error first. Then the simplified models are used in a view-dependent real-time rendering algorithm. The paper presents a new view-dependent realtime mesh simplification algorithm. The algorithm can produce simplified models in real time while controlling the rendering pixel error. Examples illustrate efficiency of the algorithm.